Evaluating the Effectiveness of Arabic Language Summative Tests in Senior High Schools: A Comprehensive Analysis - Sahrani Sahrani; Sri Herlina; Sumin Sumin; Hermansyah Hermansyah (ALSINATUNA, 2024)
The aims of this study is to describe the validity, reliability, difficulty level, differentiation power and effectiveness of the Examination of Arabic language Sumative Test Items for Class X Students of Al-Mumtaz IT Senior High School. This research uses a quantitative approach. The data obtained were analyzed using IBM SPSS statistics 23. The subjects of this study were class X students totaling 29 students. The results of the analysis of 30 multiple choice questions showed that from the validity aspect it was found that 67% were valid and 33% were invalid. From the reliability aspect, it was found that the reliability level of the items was high, namely the r coefficient of 0.864. From the aspect of difficulty level, it was found that about 63% of the items were easy, about 37% of the items were moderate. From the aspect of distinguishing power, it was found that about 60% of the items were good, about 27% of the items were not good, about 13% of the items were quite good. And from the aspect of eliminators it was found that about 56% were accepted, about 26% were rejected and about 17% were revised.